PEMBERDAYAAN KELOMPOK DUKUNGAN SEBAYA DALAM MENINGKATKAN PENGETAHUAN ORANG DENGAN HIV/AIDS TENTANG SIFILIS LATEN - Wira Daramatasia; Yuliyanik (Asosiasi Dosen Akutansi Indonesia, KEPRI, 2026)
Sexually Transmitted Infections (STIs), particularly latent syphilis, remain a public health concern requiring attention among people living with HIV/AIDS (PLWHA). Latent syphilis often presents without symptoms, which may lead to delayed diagnosis and increase the risk of complications and transmission. This community service activity aimed to improve PLWHA’s understanding of risk factors, the relationship between syphilis and HIV, prevention strategies, and early detection of latent syphilis. The activity was conducted among 35 members of the Jombang Care Center Plus Peer Support Group (KDS JCC+) in Jombang Regency through three stages: preparation, health education implementation, and evaluation. The educational session used interactive lectures supported by PowerPoint presentations, discussions, and question-and-answer sessions. Evaluation results showed that approximately 80% of participants identified syphilis prevention methods, and 75% actively participated in discussions. Continuous health education is necessary to improve health literacy and support STI prevention efforts among PLWHA. Keywords: latent syphilis; PLWHA; health education; sexually transmitted infections